Prior respiratory syncytial virus infection reduces vaccine-mediated Th2-skewed immunity, but retains enhanced RSV F-specific CD8 T cell responses elicited by a Th1-skewing vaccine formulation - Eichinger, Katherine M.; Kosanovich, Jessica L.; Perkins, Timothy N.; Oury, Tim D.; Petrovsky, Nikolai; Marshall, Christopher P.; Yondola, Mark A.; Empey, Kerry M. (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) remains the most common cause of lower respiratory tract infections in children worldwide. Development of a vaccine has been hindered due the risk of enhanced respiratory disease (ERD) following natural RSV exposure and the young age (<6 months) at which children would require protection. Risk factors linked to the development of ERD include poorly neutralizing antibody, seronegative status (never been exposed to RSV), and a Th2-type immune response. Stabilization of the more antigenic prefusion F protein (PreF) has reinvigorated hope for a protective RSV vaccine that elicits potent neutralizing antibody. While anecdotal evidence suggests that children and adults previously exposed to RSV (seropositive) are not at risk for developing vaccine associated ERD, differences in host immune responses in seropositive and seronegative individuals that may protect against ERD remain unclear. It is also unclear if vaccine formulations that skew towards Th1- versus Th2-type immune responses increase pathology or provide greater protection in seropositive individuals. Therefore, the goal of this work was to compare the host immune response to a stabilized prefusion RSV antigen formulated alone or with Th1 or Th2 skewing adjuvants in seronegative and seropositive BALB/c mice. We have developed a novel BALB/c mouse model whereby mice are first infected with RSV (seropositive) and then vaccinated during pregnancy to recapitulate maternal immunization strategies. Results of these studies show that prior RSV infection mitigates vaccine-mediated skewing by Th1- and Th2-polarizing adjuvants that was observed in seronegative animals. Moreover, vaccination with PreF plus the Th1-skewing adjuvant, Advax, increased RSV F85-93-specific CD8 T cells in both seronegative and seropositive dams. These data demonstrate the importance of utilizing seropositive animals in preclinical vaccine studies to assess both safety and efficacy candidate RSV vaccines.